A measurement of the ionization efficiency of nuclear recoils in silicon - Izraelevitch, Federico Hernán (2017)
We have measured the ionization efficiency of silicon nuclear recoils with kinetic energy between 1.8 and 20 keV. We bombarded a silicon-drift diode with a neutron beam to perform an elastic-scattering experiment. A broad-energy neutron spectrum was used and the nuclear recoil energy was reconstructed using a measurement of the time of flight and scattering angle of the scattered neutron. The overall trend of the results of this work is well described by the theory of Lindhard et al. above 4 keV of recoil energy. Below this energy, the presented data shows a deviation from the model. The data indicates a faster drop than the theory prediction at low energies.